Strengthening Mathematical Connections in Middle School Geometry: The Role of Means-Ends Analysis in Learning Cubes and Rectangular Prisms - Rahmawati, Rahmawati; Nopriana, Tri; Haqq, Arif Abdul (EDUPEDIA Publisher, 2024)
The mathematical connection abilities of middle school children are the primary subject of this study, which aims to understand how means-end analysis (MEA) policies and procedures might assist. Students need to build mathematical connection abilities that enable them to comprehend and associate various mathematical concepts to improve their ability to comprehend and apply mathematics in real-world contexts. This is an essential component of the learning process. The research uses a quasi-experimental methodology by administering tests to the control and experimental groups before and after the intervention. One group utilised the MEA tactics in the mathematics lesson, while the other group remained committed to the tried-and-true method. Data was collected through mathematical connection tests, and then statistical analysis was performed on it to determine whether or not the intervention was effective. According to the findings, students whose courses contained MEA strategies showed a considerable improvement in their mathematical connection abilities compared to the control group. This study validates that incorporating MEA approaches into the mathematics curriculum is a viable alternative for increasing students' mathematical literacy and competence. The findings of this study provide more evidence to support this idea.